Narrating The Effective Law for Foreign Direct Investment - Meliala, Aurora Jillena; Prakasa, Adinda Putri; Woods, Jonathan Andre (Indonesian Journal of International Law, 2024)
Amidst the inflation phenomenon, the government approach to raising interest rates, and the threat of global recession, Foreign Direct Investment plays a pivotal role in boosting targeted economies. However, investors impugn the investment regulations’ efficacy and alternative dispute resolutions. Specifically, in the case of International State Dispute Settlement, to be claimed as an essential process in the investment regime, it has to guarantee the rights of private parties to sue a sovereign nation under the protection of public international law – usually manifested on BIT clauses. However, this study showed. BITs do not serve to attract additional FDI. While BITs indicate the certainty of law, they have not been acknowledged to signal a safe investment climate. Potential investors seem to have little awareness or appreciation of specific BITs. In this study, we conduct empirical legal research —underlying Economic Analysis of Law and Comparative Study. The data were collected by interviewing Executive Directors and surveying investor members from various chambers of commerce in Indonesia. The ultimate aim of the approach is to contribute to a systematic understanding of shaping, strengthening, and narrating the effective law as the determinant of foreign direct investment based on empirical data and direct inquiries from investors. In this article, we give an overview of the concept of FDI and trace the original rules and core principles governing FDI, followed by outlines of the current framework for foreign investment. We then discuss varying degrees expected by investors with different characteristics, such as nationality, in discussing the effectiveness of the law.